Media politics and Islam: a constructive approach - Rahath House, Yousef; Hashim, Rosnani (The Islamic Cultural Centre and London Central Mosque, London, 2013)
The proponent of modernity and western mode envision the triumph of a one global hegemony. The entities termed as mass media are the most important strategic components of this development. The role of mass media at shaping the global citizenry in tune with a particular cultural pattern is apparent. Because of lack of concerted efforts in this field from Muslim activists, cultural invasion in the Muslim world especially among Muslim youth is greater than it is in the rest of the world. The main focus of this paper is to analyze this crisis and propose an alternative agenda in developing a new approach to reduce the negative impacts of the mass media. The approach is based on the premise that the media is currently dominated by a power structure whose interests do not concur with that of the ummah. This approach aims to counter western hegemony over the mass media and, thus over the minds of the global populace. It is specifically aimed at developing a genuine Muslim mass media culture and activism grounded on Islamic principles, thereby to defend Islamic interests.